Implementasi berpikir sejarah: Penggunaan sumber primer sejarah dalam pembelajaran di kelas - Ponco Setiyonugroho; Yusuf Budi Prasetya Santosa (Universitas Tangerang Raya, 2023)
This research aims to describe the use of primary historical sources and how the implementation of learning is carried out in the museum. The method used in this research is qualitative. Informants related to the research are class XI students and teachers who teach History subjects. Techniques in collecting data using observation, in-depth interviews, conducting documentation and the last process is data triangulation. This research uses purposive sampling which is snowball sampling, namely the subject teacher as key information and students as supporting information and the focus of researchers on the use of primary sources in learning history. The results of the research obtained are that the use of primary historical sources both in class and outside the classroom makes students able to reconstruct the past by seeing historical objects directly. In addition to class, teachers also make visits to museums to increase knowledge and understanding of history in the past. The use of primary historical sources in learning will be able to improve historical thinking.